1995
DOI: 10.1093/cercor/5.5.391
|View full text |Cite
|
Sign up to set email alerts
|

Representing Spatial Information for Limb Movement: Role of Area 5 in the Monkey

Abstract: How is spatial information for limb movement encoded in the brain? Computational and psychophysical studies suggest that beginning hand position, via-points, and target are specified relative to the body to afford a comparison between the sensory (e.g., kinesthetic) reafferences and the commands that generate limb movement. Here we propose that the superior parietal lobule (Brodmann area 5) might represent a substrate for a body-centered positional code. Monkeys made arm movements in different parts of 3D spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
219
3
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(250 citation statements)
references
References 39 publications
27
219
3
1
Order By: Relevance
“…This area has been implicated in the control of reaching to remembered locations in primates (24,25) and may play an analogous role in stepping behavior during locomotion. In vivo recordings from cats walking on a treadmill revealed that neurons from this region increase their firing rates in the 2-3 steps before the step over an obstacle (22), suggesting that this area could be involved in encoding the position of upcoming obstacles relative to the moving observer.…”
Section: Significancementioning
confidence: 99%
“…This area has been implicated in the control of reaching to remembered locations in primates (24,25) and may play an analogous role in stepping behavior during locomotion. In vivo recordings from cats walking on a treadmill revealed that neurons from this region increase their firing rates in the 2-3 steps before the step over an obstacle (22), suggesting that this area could be involved in encoding the position of upcoming obstacles relative to the moving observer.…”
Section: Significancementioning
confidence: 99%
“…These functions are anatomically segregated into specific subregions of the PPC. Medial areas, such as the medial intraparietal area and the "parietal reach region," are engaged by reaching to cued targets in the workspace (21)(22)(23)(24)(25)(26); lateral cortical regions surrounding the intraparietal sulcus (area 5 and the anterior interparietal area) signal the hand postures used to grasp specific objects (27)(28)(29)(30)(31); and areas of the medial wall of the hemisphere integrate arm and hand movements with visual signals (32,33). Motor plans and sensory attention are transformed into action by parietal interconnections with relevant premotor areas of the frontal lobe.…”
Section: I Ii I I I I Ii I I I I I I I I I I I I I I I I I I I I I mentioning
confidence: 99%
“…Electrophysiological (Andersen et al, 1987;Lacquaniti et al, 1995;MacKay and Mendonca, 1995;Sakata et al, 1985) and lesion studies (Crowne et al, 1992;Petrides and Iversen, 1979;Pu et al, 1993) in the monkey have established a role for posterior parietal cortex in coordinated visuomotor behavior such as reaching and grasping and parietal damage in humans can lead to visuomotor impairments such as an inability to use visual information in the guidance of eye or hand movements (Jeannerod et al, 1994) and failure to perform reaching movements on the basis of mirror reversed cues (Ramachandran et al, 1997). Neuroimaging studies have made it possible to fractionate different parts of the parietal cortex, according to their function and mental rotation (Alivisatos and Petrides, 1997), and mirror-reading tasks (Dong et al, 2000;Goebel et al, 1998;Kassubek et al, 2001;Poldrack et al, 1998;Poldrack and Gabrieli, 2001) have pinpointed a specific role for the superior parietal cortex in mediating visuospatial sensorimotor transformations (Dong et al, 2000;Goebel et al, 1998;Kassubek et al, 2001;Poldrack et al, 1998;Poldrack and Gabrieli, 2001).…”
Section: Introductionmentioning
confidence: 99%